The Interplay of Public/Private and Agent/Victim Dualism in Sustainable Living Practice: Indonesia’s Case - Cahyaningtyas, June (Jurnal Ilmiah Hubungan Internasional, 2024)
An examination of sustainable living practices through the lens of ecofeminism is the subject of this article. In this article, sustainable living practices refers to the actual implementation of environmentalism ideas in everyday situation. The selection of this subject is deemed significant due to the prevailing trend in environmental literature to associate it as pro-environmental behaviour that, unlike environmental activism, exclusively with the uppermiddle class, thereby rendering it feeble, apolitical, and inconsequential. This study aims to evaluate the correlation between pro-environmental behaviour and environmental action and activism by examining sustainable living practices through the lens of gender. Departing from Ecofeminism, it attempts to incorporate insights from relevant literature to enhance the discussion. Availing from exploratory field observations, this study uses Indonesia as a case studies. The study found that, in addition to the availability of social media and spiritualfactors, there are educational orientation that, related to cultural and religious aspects, bridges private/public elements as well as agents/victims division in Ecofeminism discourse. The transformation of the movement’s character from individualist to collectivist is influenced by global political dynamics, as well as showing the moral and spiritual orientation of this movement.   Keywords: sustainable living practice, ecofeminism, environmental care, pro-environmental behaviour, environmental activism